Проблеми захисту авторських прав в Інтернеті - Аврамова, О. Є.; Разіна, Ольга Ігорівна (НТУ "ХПІ", 2013)
The article deals with topical issues of copyright protection on the Internet. Described procedure for dealing with cases on copyright infringement. The methods of copyright protection on the Internet.
Keywords: інформація; інформатизація суспільства; технології комп'ютерні; порушення прав